2021
DOI: 10.3389/fmed.2021.729018
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Antitumor and Antimetastatic Potential of Induced Pluripotent Stem Cell-Based Vaccines in Cancer Immunotherapy

Abstract: Cancer is maintained by the activity of a rare population of self-renewing “cancer stem cells” (CSCs), which are resistant to conventional therapies. CSCs over-express several proteins shared with induced pluripotent stem cells (iPSCs). We show here that allogenic or autologous murine iPSCs, combined with a histone deacetylase inhibitor (HDACi), are able to elicit major anti-tumor responses in a highly aggressive triple-negative breast cancer, as a relevant cancer stemness model. This immunotherapy strategy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Innate immune cells could trigger the adaptive immune responses, and understanding of cancer-intrinsic processes will supply the exploration and development of immunotherapy ( 26 , 27 ). Cancer-associated fibroblast was reported to induce cancer cell proliferation, invasion, and metastasis through various pathways ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune cells could trigger the adaptive immune responses, and understanding of cancer-intrinsic processes will supply the exploration and development of immunotherapy ( 26 , 27 ). Cancer-associated fibroblast was reported to induce cancer cell proliferation, invasion, and metastasis through various pathways ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-associated fibroblast was reported to induce cancer cell proliferation, invasion, and metastasis through various pathways ( 28 , 29 ). Moreover, Tregs that expressed the transcription factor Foxp3 could possess importance in immune homeostasis ( 26 , 30 ). In this study, we found that LIAS expression was strongly correlated with the infiltration of immune cells, including B cell, cancer-associated fibroblast, T cell CD8+, DC, macrophage, and Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immune responses may be triggered by innate immune cells, and research into and the development of immunotherapy will be aided by knowledge of the internal workings of cancer ( 32 , 33 ). According to Schalper et al and Bremnes et al ( 34 , 35 ), type I immune responses are typically associated with CD8 + T cells and T cells triggered by CD4 + type 1 T helper cells, and they are associated with a positive prognosis for lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been con rmed that the occurrence, development and treatment of tumors are relevant to tumor immune cell in ltration (20,21). In our study, we found that the expression of DBT was signi cantly positively related with immune in ltration level in diverse cancer types, included T cell CD8+ in PAAD and UM, neutrophil in BRCA, PRAD and KIRC, cancer associated broblast in HNSC, PAAD, STAD and THYM, endothelial cell in COAD, HNSC, KIRC and LUAD.…”
Section: Discussionmentioning
confidence: 99%